If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + -26 = 9 Reorder the terms: -26 + N = 9 Solving -26 + N = 9 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + N = 9 + 26 Combine like terms: -26 + 26 = 0 0 + N = 9 + 26 N = 9 + 26 Combine like terms: 9 + 26 = 35 N = 35 Simplifying N = 35
| 26-n=9 | | 12x-4=4x+4 | | 1.5n=75 | | y=-7x+1 | | m-1.8=6 | | 6x+1=4x+3 | | 81=3n | | 0.9-x=1 | | x^3+18x^2+71x+40=0 | | u^2-u-7=0 | | -14=7x | | -15=-5x | | 4X^3-18X^2+16X+3=0 | | -8=x+12 | | 20+8q=-42 | | 21+x=-9 | | -16=x+25 | | x-7.9=3.8 | | 2(x+6)=4x-6 | | n^4+2n^3-n^2-2n=0 | | a-7=-3 | | -7-6=21-2x | | 240=22r+r^2 | | 3(x+5)=x+25 | | 5x+7=x+23 | | 5x+10=8x-11 | | 1000a+(663)=919a | | 2+b=8 | | (3x-5)[2]=19 | | 150+.50n=255 | | 5(4z-1)-2(Z+2)=14(Z+1) | | 2(x+8)-x=2(3-x)-7 |